2018
DOI: 10.29121/granthaalayah.v6.i10.2018.1187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Autocratic Leadership Style on Job Performance of Subordinates in Academic Libraries in Port Harcourt, Rivers State, Nigeria

Abstract: The study focused on the impact of autocratic leadership style on job performance of subordinates in academic libraries in Port Harcourt, Rivers State, Nigeria.  The research design was a survey. The respondents were the 74 professional and para-professional staff working in the libraries studied.  Data collection was through questionnaire.  instrument titled “Autocratic Leadership Style on Job Performance of Subordinates in Academic Libraries (ALSJPSAL)” consisting of five (5) item statements. Analysis was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This is because during work from home employees are not directly supervised by superiors, employees do a job because they already have their respective duties and responsibilities towards their work, then the leadership style has no effect on improving employee performance. This study is in line with research conducted by Sebastian (2017) and Rathore et al (2017), but not in line with research conducted by Dolly & Nonyelum (2018). The participatory leadership style at PT Hanwa Indonesia can be accepted by all employees, but in this study the leader could not give the employee morale.…”
Section: Data Analysis and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is because during work from home employees are not directly supervised by superiors, employees do a job because they already have their respective duties and responsibilities towards their work, then the leadership style has no effect on improving employee performance. This study is in line with research conducted by Sebastian (2017) and Rathore et al (2017), but not in line with research conducted by Dolly & Nonyelum (2018). The participatory leadership style at PT Hanwa Indonesia can be accepted by all employees, but in this study the leader could not give the employee morale.…”
Section: Data Analysis and Discussionsupporting
confidence: 82%
“…Employees tend to experience increased performance when they expect and receive rewards and witness punishment as a consequence of their actions. Meanwhile, Dolly & Nonyelum (2018) in their research stated that the autocratic leadership style had a significant negative effect on employee performance. Autocratic leaders tend to limit employee performance.…”
mentioning
confidence: 99%
“…In another instance, Wang's, et al (2019) study showed no correlation between authoritarian leadership and employee performance. On the contrary, the study of Kalu and Okpokwasili (2018) showed otherwise. In terms of organizational change, on one hand, this does not correlate with autocratic leadership (Du, et al 2019).…”
Section: Introductionmentioning
confidence: 89%
“…This is when the leader makes the decision for the whole group and does not take his/her employees' input into consideration. Consequently, autocratic leadership could cause contentious behavior, guarded communication, low productivity, and a lack of creativity in the group (Dolly & Okpokwasili, 2018). Thus, the autocratic leadership style is effective only in certain situations and is not the best to use to maintain relationships between subordinates and managers.…”
Section: Autocratic Leadershipmentioning
confidence: 99%